Synthesis and characterisation of triphenylmethine dyes for colour conversion layer of the virtual and augmented reality display. (August 2022) - Jang, Seong Hyun; Lee, GeonHo; Lee, Sang Yoon; Kim, Se Hun; Lee, Woosung; Jung, Jae Woong; Kim, Jae Pil; Choi, Jun
Abstract: Five triphenylmethine dyes were designed and synthesised for the blue colour conversion layer of virtual and augmented reality displays. To form subpixel patterns suitable for high-brightness microdisplay panels, the prepared dyes must exhibit high solubility, colour strength, durability, and colour purity. For this purpose, three major strategies were introduced: dimerisation of triphenylmethine, chlorination, and counterion exchange. The electrostatic and spectroscopic characteristics of the synthesised dyes were investigated and predicted using computational calculations. The counter anion-modified dyes exhibited superior optical properties and thermal- and photo-stabilities compared to their parent dyes. The modified dyes also showed enhanced solubility toward industrial solvents because of their highly twisted chemical structures and weakly coordinating counter anion substituents. The synthesised dyes were chlorinated to optimise blue colour tuning and prevent the agglomeration of dyes. DTPM-Cl-HFPSI was selected as the main colourant, and EV-HFPSI was selected as the colour-matching colourant to manufacture optimal deep blue colour resists. The optimised spin-coated films exhibited high transmittance in the blue region and excellent properties in terms of brightness and colour purity by absorption over a wide and appropriate visible region. Graphical abstract: Image 1 Highlights: Five novel triphenylmethine dyes were synthesised and suitably fabricated into colour conversion layer in microdisplays. Electric surface potential and frontier orbitals of the dyes were investigated via computational calculations. Weakly coordinating anion was introduced into the dyes, leading to improved solubility, durability, and optical property. Ideal blue transmittance spectrum was obtained by colour matching of the synthesised dyes.